PERILAKU NONVERBAL JESSICA DALAM SIDANG PERADILAN - Fitri, Nidya (Jurnal KATA, 2018)
Jessica’s nonverbal behavior has been phenomenal in recent years. Media coverage of court room hearing Live and watched by the audience. The role of language is very important in deciding a judge decision. Nonverbal behavior is a part of language evidence in the court room. This research is aimed at describing and explaining function and meaning of Jessica’s nonverbal behavior. This research used qualitative descriptive method by using observational method and pragmatic approach. The object of this research was court room taken from KPI (Indonesia Broadcasting Commission.). The result of this research showed that two from the five language functions, i.e. representative function and directive function. Based on Jessica’s nonverbal behavior meaning found on from five nonverbal behavior, i.e, the meaning of hand gesture. The function and the meaning of Jessica’s nonverbal behavior was committed Jessica to prove her innocence action.